Determination of Financial Performance in Predicting Profit Growth of Consumer Goods Industry Companies - Rolia Wahasusmiah (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
The phenomenon of profit growth is not just a number, but a critical indicator in measuring the success of a company's performance. It is a tangible reflection of how effectively and efficiently the management parties have managed the resources owned by the company. Therefore, financial analysis is not just a tool, but a necessity to analyze and estimate profits and make decisions on the growth of profits to be achieved in the future. Factors that can influence earnings growth are Total Asset Turnover (TAT), Net Profit Margin (NPM), Return on Assets (ROA), Debt to Equity Ratio (DER), and Working Capital to Asset (WCTA). The problem in this study is how the influence of TAT, NPM, ROA, DER, and WCTA on profit growth. Based on the results of the study, it can be seen that Total Asset Turnover (TAT), Net Profit Margin (NPM), Return on Assets (ROA), Debt to Equity Ratio (DER), and Working Capital to Asset (WCTA) do not affect profit growth.